CORRELATION OF RADIOGRAPHIC DAMAGE AND METABOLIC SYNDROME IN SPONDYLOARTHRITIS: A CROSS-SECTIONAL STUDY - GUNAWAN, HENDRA; MUDJANARKO, SONY WIBISONO; AWALIA; RAHMAWATI, LITA DIAH; SOEROSO, JOEWONO; PRANOTO, AGUNG (International Journal of Applied Pharmaceutics, 2019)
Background: Cardiovascular complication remains the long-term complications in spondyloarthritis (SpA). Previous studies revealed that metabolic syndrome is the risk factor of cardiovascular in SpA patients. Previous studies also revealed that the prevalence of the metabolic syndrome is 34.9– 45.7% in SpA patients. However, previous studies also revealed the controversy of the correlation of SpA’ disease activity with metabolic syndrome. Aim: The aim of the study was to investigate the correlation of SpA’ radiographical damage measured with a modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) score with metabolic syndrome in SpA patients, which routinely visited Rheumatology Outpatient Department in Dr. Soetomo General Hospital. Methods: An observational study with cross-sectional design with consecutive sampling technique was conducted in July–October 2018. All SpA patients who fulfilled the inclusion criteria were included in this study. Data analysis was performed with SPSS v21.0. Results: There were 33 SpA patients (10 males and 23 females) included in this study. The average age was 48.18±12.27 years-old. The average mSASSS score was 24,36 (K:0.93, p:0.00). Metabolic syndrome was diagnosed in 54.5% patients with 100% patients had central obesity, 66.7% had increased blood pressure, 61.5% had impaired fasting glucose, 55.6% had increased triglycerides, and 77.8% had decreased high-density lipoprotein cholesterol. Positive correlation between mSASSS score and metabolic syndrome was observed (r:0.510, p:0.002). Conclusion: A correlation between SpA disease activity measured with mSASSS score and metabolic syndrome was observed. Therefore, routine metabolic syndrome screening is strongly suggested for SpA patients.